Pengaruh Citra Merek, Kualitas Layanan, dan Digital Banking Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Sebagai Variabel Intervening Pada PT Bank Syariah Indonesia Cabang Pekalongan Pemuda - Mochamad Yusuf; Muhammad Aris Syafi'i; Tamamudin Tammamudin (ISLAMIC BUSINESS and FINANCE, 2023)
Customer loyalty is a commitment to using the product. Customer loyalty is achieved through satisfaction, brand image, service quality, and digital banking. This study aims to determine the effect of brand image, service quality, and digital banking on customer loyalty through customer satisfaction as an intervening variable at Bank Syariah Indonesia Pekalongan Pemuda. This research is quantitative research. The population amounted to 48,200. Sample of 100 respondents with the slovin formula, standard error 10%. Accidental sampling technique using a questionnaire. Data analysis techniques in the form of instrument tests, classical assumption tests, path analysis, hypothesis testing and coefficient of determination tests. The results showed that brand image significantly affects satisfaction with a beta value of 0.421 and a significance of 0.00. Service quality has no effect and is not significant to customer satisfaction with a beta value of -0.029 and a significance of 0.545. Digital banking has no effect and is not significant to customer satisfaction with a beta value of -0.002 and a significance of 0.964. Brand image significantly affects customer loyalty with a beta value of 0.436 and a significance of 0.001. Service quality has no effect and is not significant to customer loyalty with a beta value of 0.091 and a significance of 0.194. Digital banking has a significant effect on customer loyalty with a beta value of 0.392 and a significance of 0.00. Customer satisfaction significantly affects customer loyalty with a beta value of 0.504 and a significance value of 0.001. Customer satisfaction mediates the effect of brand image on customer loyalty with a t value = 2.178. Customer satisfaction does not mediate the effect of service quality on customer loyalty with a t value of -0.454. Customer satisfaction does not mediate the effect of digital banking on customer loyalty with a t value of 0.037.Keywords: Brand Image, Service Quality, Digital Banking, Customer Satisfaction, and Customer Loyalty.